The Abbasid State's Contribution to Education: History, Policy, and Development of Islamic Educational Institutions - Yazida Ichsan; Yusuf Hanafiah; Fadhlurrahman Fadhlurrahman; Supitri Okfia (At-Taqaddum, 2023)
This study aims to describe the contribution of Abbasid civilization to education both covering Abbasid history, policies related to scientific development, and developing educational institutions. This research is a literature research by emphasizing historical aspects with heuristics, criticism, interpretation and histography steps. The results of the study showed that there were several policies implemented by the government to develop science and civilization which included translation projects, rihlah 'ilmiyyah and  the construction of educational institutions which included libraries, kuttab, mosques, madrasas, art studios, bookstores, observatories, ribath and zawiyyah. When contextualized with Islamic education today, there are several alternatives offered by the Abbasid State. First, in addition to using a normative approach, an experimental approach in education is needed as a solutive alternative to facing industrial challenges.  Second, to form educated people, there needs to be a synergy of all elements, not just educational institutions.  Third, Islamic educational institutions must have a concentration in certain sciences on the basis of Islamic norms.